Gender perspectives in estimation of rates and determinants of adoption of the infection and treatment method of vaccination against East Coast Fever among smallholder cattle keepers in Uasin-Gishu County, Kenya - Humphrey, Jumba (International Livestock Research Institute, 2018)
Presented by Jumba Humphrey (ILRI/LIVESTOCK), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.